Linguistic concepts across languages: The category of epistemic adverbs in English and Polish - Rozumko, Agata (Yearbook of the Poznan Linguistic Meeting, 2016)
The category of epistemic adverbs has recently received increased attention in both Anglophone and Polish linguistics, but English–Polish contrastive research in this area has so far been rather fragmentary. English and Polish grammars differ considerably in the ways they classify epistemic adverbs. The differences largely result from the different understanding of adverbs as a category, which in English grammar tends to be presented as broad and heterogeneous while in Polish grammar – rather narrow and uniform. Polish equivalents of English epistemic adverbs are classified as particles – a distinct word class with its own characteristic properties. This paper presents an overview of approaches to epistemic adverbs taken in Anglophone and Polish linguistics with the aim of identifying their convergent points and suggesting a framework for a contrastive analysis. In the case of Anglophone research, the focus is largely on discourse studies because epistemic adverbs are usually seen as a discourse category. In Polish linguistics, however, they are analysed within different theoretical frameworks, which is why the discussion will not be limited to one specific methodological school. Reference is also made to more general issues, such as the treatment of adverbs as a category.